Characterization and Expression of E2 Glycoprotein of Classical Swine Fever Virus in a Eukaryotic Expression System - Ratta, Barkha (Springer-Verlag, 2010)
Classical swine fever (CSF) is an economically important Office International des Epizooties (OIE) list A disease of swine characterized by high fever and multiple haemmorhages. The E2 glycoprotein of CSFV is immunogenic and induces neutralizing antibodies against CSFV. In the present study, complete coding region of the E2 gene from Indian virulent field isolate (Mathura) was amplified by reverse transcription-polymerase chain reaction (RT-PCR) and subsequently cloned into a mammalian expression vector; pcDNA3.1(+) at BamHI and XbaI site. The recombinant plasmid; pcDNA.E2.CSFV. was confirmed by restriction enzyme digestion. The pcDNA.E2.CSFV. transfected Vero cell expressed E2 protein which was confirmed by western blotting, immunoperoxidase and indirect immunofluorescent tests. Additionally, flow cytometry analysis also confirmed that 15% of transfected Vero cells expressed the E2 glycoprotein compared to mock or vector alone transfected cells. Further study is under way to evaluate recombinant pcDNA.E2.CSFV. Mathura clone as DNA vaccine against CSFV.